MINERALIZATION RATES OF PEAT FROM ERODING PEAT ISLANDS IN RESERVOIRS - St.Louis V.L.; Partridge A.D.; Kelly C.A.; Rudd J.W.M. (My University, 2003)
Reservoirs are sources of greenhouses gases to the atmosphere, primarily due to organic carbon mineralization in flooded plants and soils to carbon dioxide (CO2) and methane (CH4). Floating peat islands are common in reservoirs that inundated peatlands. These islands can decompose on mass, or small pieces of peat can erode from islands to decompose in the water column or on the bottom of reservoirs. Here we used large 450 liter sealed enclosures to measure mineralization rates of small peat pieces and larger peat blocks collected from floating peat islands. Mineralization rates were calculated by quantifying dissolved inorganic carbon (DIC), CO2 and CH4 accumulation within the water and headspace of the enclosures over time. We found that peat did decompose under water, but rates of mineralization of peat pieces were not different than rates of mineralization of larger peat blocks. Mineralization rates ranged between 59 and l40 μg C g-1 d-1. Peat pieces acidified the water, shifting the bicarbonate equilibrium to almost exclusively dissolved CO2, which was then readily able to flux to the atmosphere. We estimated that 2.4-5.6% of peat carbon was mineralized annually, suggesting that fluxes of CO2 and CH4 from reservoirs that flood peatlands could last at minimum 18-42 years from this carbon source alone.
Keywords: FLOATING PEAT ISLANDS; GREENHOUSE GAS EMISSIONS; PEAT DECOMPOSITION; RESERVOIRS